Cerebral Ovine Herpesvirus 2 Infection of Cattle Is Associated With a Variable Neuropathological Phenotype. Issue 2 (March 2021) - Hierweger, Melanie M.; Boujon, Céline L.; Kauer, Ronja V.; Meylan, Mireille; Seuberlich, Torsten; Oevermann, Anna
Cross-species infection with ovine herpesvirus 2 (OvHV-2) in cattle causes malignant catarrhal fever (MCF). MCF may involve the central nervous system (CNS) with necrotizing arteritis and/or vasculitis described to be unique to MCF and discriminatory compared to other viral CNS infections. However, a systematic histopathological characterization of the neural form of MCF in cattle is lacking. We examined medulla oblongata ( n = 9) or the entire brain ( n = 9) of 18 cattle in which OvHV-2 was identified by quantitative polymerase chain reaction (qPCR), in order to pinpoint potential variations in neuropathology. In 2/18 animals (11%) no lesions were identified, while 16/18 cattle (89%) had brain lesions of varying severity. Presence and quantities of OvHV-2 nucleic acid were determined by in situ hybridization and qPCR, respectively, and were related to the severity of lesions. Fifteen of 18 animals (83%) showed vasculitis, which was mainly of the lymphohistiocytic type, while pathognomonic necrotizing arteritis was only rarely present. Neuroparenchymal lesions included gliosis and/or neuronal changes in 7/16 brains with lesions (44%). The number of CD3+ lymphocytes was highest in animals with simultaneous vascular and neuroparenchymal lesions and high viral genome load. In one animal, OvHV-2 was exclusively observed in CD3+ lymphocytes but not in neurons or microglia. In conclusion, the neuropathological phenotype of bovine MCF in the brain was variable. In some cases, lesions mimicked neurotropic viral encephalitis, while pathognomonic necrotizing arteritis was not a consistent feature of neural MCF. Therefore, molecular detection of OvHV-2 is warranted in the presence of nonsuppurative encephalitis and in the absence of necrotizing arteritis.